An Analysis of Business Marketing Strategies Using the Analytical Hierarchy Process (AHP): A Case Study of Dapur Ibuk MSME - Hamsiah Hamsiah; Nurafni Jami Putri; Adek Irma Rosi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the marketing strategy of the MSME